Ultra tough and high resilience mechanochromic fibres for real world stress detection - Yu Jin Jeong; Youngeun Lee; Taekyung Won; Ji Won Lee; Youngho Eom; Dae Seok Kim (Nature Communications)
Abstract Cholesteric liquid crystal elastomer fibres gain considerable attention as promising candidates for mechanochromic smart textiles across various domains, ranging from fashion to healthcare. However, intrinsically high hysteresis of cholesteric liquid crystal elastomer during stress relaxation necessitates a time-lag between successive stimulus detections, thereby constraining the practical use in real-world systems. Here, we develop high-tough and low-hysteresis mechanochromic fibres capable of effectively detecting ultra-fast deformations at practical levels. By utilizing a thermoplastic elastomer as a core fibre and cholesteric liquid crystal elastomer as a sheath, we develop sheath-core composite fibres. The cholesteric liquid crystal elastomer sheath-core fibres preserve remarkable optical properties of cholesteric liquid crystal elastomer sheath while improving mechanical properties, including high strength (100.9 MPa), toughness (2.7 × 102 MJ m−3), and ultra-fast resilience (60% strain at 49.98 cm s−1 strain speed) due to the thermoplastic elastomer core. We demonstrate on-demand mechanochromic fibres with tuneable moduli of thermoplastic elastomer core, expanding the fields of smart textile from single fibre to dynamic sensory environment.